Rafinose na alimentação de leitões recém-desmamados - Daniel, Everton [UNESP] (2014)
Commonly used ingredients in piglets feed, such as corn and soybean meal have galacto-oligosaccharides (Gos), as raffinose, which do not have their effects on nutrition of piglets fully understood. One study was conducted using newly weaned pigs, from 21 to 63 days old, distributed into a randomized complete block design with five treatments. It was elaborated a diet containing low Gos levels, and added to this diet purified raffinose (0, 0.75, 1.50 and 2.25%). The fifth diet was elaborated with corn and soybean meal (CSBM) containing usually Gos levels in piglets diets. Were evaluated the digestibility of nutrients and energy, digesta transit time (DTT), digestive organs weight, performance, diarrhea incidence, gut morphology, and intestinal pH and microbiology. The total tract digestibility of nutrients and energy, as well DTT were linear decreased when the raffinose levels increased. The same result was observed to the amino acids, mainly, the nonessentials, however, the minerals digestibility were not affected. The total tract digestibility of nutrients and energy of CSBM diet were lower than the diets containing 0 and 0.75% of raffinose. The highest caecum weight was estimated to 0.76% of raffinose level. The feed intake and final weight, at 49 days old had a quadratic effect, while feed conversion ratio was linearly reduced when levels of raffinose increased. The diarrhea incidence was not affected by diets. The villi heights linearly increase with raffinose addiction. The gut content of lactic acid bacteria was not affect by raffinose levels, however, a fewer number of E. coli were estimated to 1.23 and 1.40% of raffinose levels in jejunum and caecum, respectively. In conclusion, the raffinose decreases the digestibility coefficients of nutrients and energy and digesta transit time; improves the performance, does not caused diarrhea in newly weaned piglets and also decreases the intestinal E coli populations